PENGARUH KURIKULUM MERDEKA TERHADAP DISIPLIN BELAJAR SISWA KELAS X SMA NEGERI 1 TAWANGSARI KABUPATEN SUKOHARJO TAHUN AJARAN 2025/2026 - Cindy Spire Prasetya; Mu'in Abdullah; Yuni Safitri (STKIP Pesisir Selatan, 2026)
This study aims to (1) determine the level of implementation of the Independent Curriculum. (2) determine the level of student learning discipline. (3) and determine the effect of the implementation of the Independent Curriculum on the learning discipline of class X students of SMA Negeri 1 Tawangsari in the 2025/2026 Academic Year. The researcher used a quantitative descriptive approach. The data collection technique used a Likert scale questionnaire. Sampling used probability sampling. The data analysis technique used descriptive statistics. Hypothesis testing used Pearson product moment and simple linear regression. The results of the study showed that: (1) the level of Independent Curriculum implementation was in the moderate category with an average score of 47.20 (2) the level of students’ learning discipline was in the moderate category with an average score of 37.69 and (3) there was a positive and significant relationship between the implementation of the Independent Curriculum and students’ learning discipline, with a correlation value of r = 0.593 and a contribution of 35.2% (coefficient of determination, R² = 0.352), indicating that students’ learning discipline is influenced by the implementation of the Independent Curriculum.